The synthesis of solutions for the prevention and suppression of forest fires - I.R., Shegelman; A. S., Shtykov; Ivashnev M.V., Vasilev A. S, (Opción, 2019)
The study aims to investigate the synthesis of solutions for the prevention and suppression of forest fires. The research is based on the author’s methodology of functional technological analysis with the implementation of scientific, technical and patent searches. As a result, the technical solution is aimed at increasing the efficiency of extinguishing forest fires by creating a shock wave of tremendous strength and amplitude to bring down the fire flame. In conclusion, an important way to solve the problem is the accelerated development of innovative technologies and techniques for the prevention and suppression of forest fires.